PROBLEMATIKA TANGGUNG JAWAB PENGUSAHA KAPAL PERAIRAN DARAT TERHADAP PENGGUNA JASA ANGKUTAN - Kamasi, Andrie (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTÂ That in the ordinance of 1935 ships has been specified on the requirements of the vessel's eligibility in making the voyage as well as the requirements in the form of licenses issued by the Indonesian Classification Bureau or issued by the government c.q. Syahbandar and Head of Transportation Office. For and to be safe in the voyage, the surface water vessels shall be equipped with letters of vessels which are guarantees for the eligibility of the vessel to sail in accordance with the requirements specified in the Orders of 1935 ships and the Ordinance of 1927 inland vessels as well as the rules of their operation . A ship is said to be worthy of a screen to transport passengers and / or goods if it has a certificate of perfection. This is mentioned in Article 6 paragraphs (1) and (3) Ordinance of ships of 1935. In the conduct of transport in inland waters especially freight transport, the carrier and freight forward generally never make a written transport agreement but is made orally, rights and obligations of the parties are practically not illustrated clearly. In the event of any adverse event of money to the sending party because of damage, loss or loss of an item due to errors or omissions of the carrier, the carrier usually still compensates, although not as much as the actual losses it incurred. In the case of carriage of passengers (persons), the carrier shall always be held liable for losses suffered by a passenger if he is injured or dead, without any obligation to the passenger or his heirs to prove his right to remedy, sufficient when he postulates that he suffered injuries caused by the transport. The presumption only disappears if the carrier can prove that the loss occurred not by mistake on his part or inevitably (overmacht) or due to passenger fault it self, is problem the continue and solution not yet. Keywords: Sailing Ships, Transportation Issues, Transportation of Goods and People